2011
DOI: 10.4315/0362-028x.jfp-10-365
|View full text |Cite
|
Sign up to set email alerts
|

Use of Natural Ingredients To Control Growth of Clostridium perfringens in Naturally Cured Frankfurters and Hams

Abstract: A major concern for processed meats marketed as natural/organic is that they do not contain nitrite in concentrations known to be most effective for inhibiting foodborne pathogens. Supplemental treatments to increase the level and consistency of antimicrobial protection in these products may be important to provide consumers with the degree of safety that they have come to expect from conventionally cured meats. Therefore, the objective of this study was to identify and test ingredients that might improve proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 9 publications
6
22
0
Order By: Relevance
“…Schrader (16) found that these antimicrobials reduced L. monocytogenes growth on naturally cured frankfurters, with antimicrobial B exhibiting greater inhibitory effects and major differences in growth that were observed by day 28 (of 120 days total) of storage at 4°C. However, in comparing the same natural curing agents and antimicrobials in similar treatment combinations, Jackson and others (11) found that the natural curing method used to produce naturally cured ham and frankfurters had a greater influence than did antimicrobials on inhibiting Clostridium perfringens. These differences in pathogen inhibition between the organisms are likely explained by differences in nitrite tolerance (24).…”
Section: Resultsmentioning
confidence: 95%
“…Schrader (16) found that these antimicrobials reduced L. monocytogenes growth on naturally cured frankfurters, with antimicrobial B exhibiting greater inhibitory effects and major differences in growth that were observed by day 28 (of 120 days total) of storage at 4°C. However, in comparing the same natural curing agents and antimicrobials in similar treatment combinations, Jackson and others (11) found that the natural curing method used to produce naturally cured ham and frankfurters had a greater influence than did antimicrobials on inhibiting Clostridium perfringens. These differences in pathogen inhibition between the organisms are likely explained by differences in nitrite tolerance (24).…”
Section: Resultsmentioning
confidence: 95%
“…After inoculated frankfurters and ham were stored for 10 days at 20°C, results showed both the uncured (0 ppm of nitrite) treatments and the treatments cured with a natural source of nitrite (equivalent to -50 ppm ingoing) had reached nearly 7 log CFU/g C. perfringens, indicating, as in this study, that the relatively low nitrite concentration con tributes negligible antimicrobial effect as a sole ingredient inhibitor. Jackson et al (9) also evaluated two antimicro bials, a lemon-cherry-vinegar blend (1.4% in frankfurters and 0.7% in ham) and a CSV blend (unreported usage in frankfurters and 3% in ham), tested in combination with naturally generated nitrite (-50 ppm), and showed varied degrees of inhibition of C. perfringens growth. In inoculated frankfurters, for example, 1.4% vinegar-lemon-cherry blend with natural nitrite resulted in 0.49 ± 0.24 log C. perfringens across sampling days, whereas populations of 1.49 + 0.29 log were observed in frankfurters containing a CSV blend with natural nitrite.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrite affects the germination and outgrowth of C. perfringens spores in different types of meat products, and it has been reported that conventionally cured meat products, which have nitrite supplements, showed inhibition of the growth of C. perfringens (29,30). However, commercially available organic meat products have the potential to support growth of C. perfringens (31,32). Although nitrite is a very good antimicrobial agent, unfortunately its use in food products is limited due to its ability to form carcinogenic derivatives (33).…”
Section: Chemical Agentsmentioning
confidence: 99%